Effects of dietary fiber from brown algae on energy intake: a review - Xia QIU; Fa-he WANG; Zhan-yi SUN (Editorial Office of Chinese Journal of Public Health, 2022)
Obesity is a risk factor for many diseases. Energy intake plays an important role in the development of obesity. Studies have shown that increasing the amount of dietary fiber in diet can boost gut motility, increase satiety, and reduce energy intake. Alginate is a marine fiber extracted from the cell wall of alga. Recently, researchers have paid much attention to the role and mechanism of alginate in controlling dietary energy. In the study, mechanisms and influencing factors for dietary fiber from algae in regulation on energy production, storage and consumption were reviewed.